2021
DOI: 10.1016/j.biopha.2021.111980
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17A (IL-17A): A silent amplifier of COVID-19

Abstract: One of the hallmarks of COVID-19 is the cytokine storm that provokes primarily pneumonia followed by systemic inflammation. Emerging evidence has identified a potential link between elevated interleukin-17A (IL-17A) levels and disease severity and progression. Considering that per se , IL-17A can activate several inflammatory pathways, it is plausible to hypothesize an involvement of this cytokine in COVID-19 clinical outcomes. Thus, IL-17A could represent a marker of disease progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 67 publications
(73 reference statements)
2
35
2
Order By: Relevance
“…In contrast to our study, elevated levels of serum IL-17A were reported to be associated with the disease severity and progression [32] . Although the inflammatory markers are considered non-specific in patients with COVID-19 infection, serum levels of IL-6 and CRP were reported to predict the outcome in patients with COVID-19 infection [33] .…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our study, elevated levels of serum IL-17A were reported to be associated with the disease severity and progression [32] . Although the inflammatory markers are considered non-specific in patients with COVID-19 infection, serum levels of IL-6 and CRP were reported to predict the outcome in patients with COVID-19 infection [33] .…”
Section: Discussioncontrasting
confidence: 99%
“…Released from activated T H 17 cells, IL-17 has been identified as a potent effector cytokine towards pulmonary hyperinflammation during COVID-infection. IL-17 exerts its effect through activation of multiple signalling pathways and transcription factors, particularly NF k B, promoting additional pro-inflammatory cytokines and chemokines of alveolar and epithelial origin, hence leading to potentially lethal cytokine storm ( 27 28 ). Akin to IL-17, significant expression of TNFα by infected tissues, innate immune cells, and T H 17 detected in serum showed a strong positive correlation to COVID-19 severity and mortality ( 29 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Published reports explain there was an altered TNF-α response seen during COVID-19 infection [ 40 ] IL-17 play a key role in the pathogenesis of multiple inflammatory and autoimmune disorders [ 42 ]. Studies have also shown that increased levels of IL-17A are a silent amplifier of the COVID-19 immune responses [ 43 ]. In our study, we evaluated the dynamics and durability of SARS-CoV-2 antigen specific T cell responses in early and late COVID-19 convalescent individuals.…”
Section: Discussionmentioning
confidence: 99%